2018
DOI: 10.3389/fnbeh.2018.00289
|View full text |Cite
|
Sign up to set email alerts
|

Is Empathy for Pain Unique in Its Neural Correlates? A Meta-Analysis of Neuroimaging Studies of Empathy

Abstract: Empathy is an essential component of our social lives, allowing us to understand and share other people's affective and sensory states, including pain. Evidence suggests a core neural network—including anterior insula (AI) and mid-cingulate cortex (MCC)—is involved in empathy for pain. However, a similar network is associated to empathy for non-pain affective states, raising the question whether empathy for pain is unique in its neural correlates. Furthermore, it is yet unclear whether neural correlates conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
150
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(189 citation statements)
references
References 47 publications
22
150
3
Order By: Relevance
“…As findings by Gu et al (Gu, Liu, et al, 2013) suggested that the left AI might be a key node in a neural network that serves as the anatomical basis for cognition-emotion integration. Two meta-analyses of empathy studies provide indirect supporting evidence that the left AI might be active both in the affective-perceptual form of empathy and the cognitive-evaluative form of empathy (Fan et al, 2011;Timmers et al, 2018). The present findings do not confirm that the left AI only plays a role in cognitive empathy.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…As findings by Gu et al (Gu, Liu, et al, 2013) suggested that the left AI might be a key node in a neural network that serves as the anatomical basis for cognition-emotion integration. Two meta-analyses of empathy studies provide indirect supporting evidence that the left AI might be active both in the affective-perceptual form of empathy and the cognitive-evaluative form of empathy (Fan et al, 2011;Timmers et al, 2018). The present findings do not confirm that the left AI only plays a role in cognitive empathy.…”
Section: Discussioncontrasting
confidence: 89%
“…The present investigation revealed an inverse relationship between GMV in the AI and trait empathy; that is, decreased brain volume in the bilateral AI was associated with increased trait empathy scores. Additionally, in a whole-brain analysis, the peculiar inverse relationship not only show in the AI, but also in other brain regions (e.g., MCC, the precuneus, IFG, the amygdala, MFG, SMA, AG, SMG, and IPL) which is consistent with recent metaanalyses highlighting these regions as core networks involved in empathy (Fan et al, 2011;Timmers et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The components encompassed a network primarily including the inferior and lateral parietal regions, the postcentral and supramarginal gyrus, AI and adjacent IFG as well as the dmPFC and adjacent MCC regions. Previous metaanalytic results from studies employing subtraction contrasts revealed a highly overlapping network engaged during empathic responses, including pain empathy (Fan et al, 2011;Lamm et al, 2011;Timmers et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The anterior insula (AI) and the anterior cingulate cortex (ACC) -which represent core nodes of the pain matrix (Price, 2000;Wager et al, 2013) and larger salience network (Uddin, 2015)respond both during experiencing first-hand pain as well as observing pain in others (Bernhardt & Singer, 2012;Jackson, Rainville, & Decety, 2006;Singer et al, 2004). Meta-analyses of fMRI studies have furthermore confirmed robust engagement of the AI and cingulate regions, specifically dorsal ACC and anterior portions of the midcingulate cortex (MCC) during empathic processes, including pain empathy (Fan, Duncan, de Greck, & Northoff, 2011;Lamm, Decety, & Singer, 2011;Timmers et al, 2018). Empathy is a multifaceted socialcognitive process which employs several emotional and cognitive systems (Shamay-Tsoory, 2011), such as the mirror-neuron system underlying simulation and affect sharing which comprises the inferior frontal gyrus (IFG) and inferior parietal lobule (IPL) (Iacoboni & Dapretto, 2006), mentalizing and self-other discrimination which additionally engage the temporoparietal junction (TPJ), the medial prefrontal cortex (mPFC), the posterior cingulate cortex (PCC) and the medial temporal lobe (MTL) (Kurczek et al, 2015;Saxe & Kanwisher, 2003;Schurz, Radua, Aichhorn, Richlan, & Perner, 2014;Uddin, Iacoboni, Lange, & Keenan, 2007).…”
Section: Introductionmentioning
confidence: 95%